EFFECT OF CYLINDER SURFACE ROUGHNESS TO THE DISTANCE FORMATION OF VORTEX - Heriyani, Oktarina; Mugisidi, Dan; Hilmi, Irfan (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2020)
Reduction of cylinder surface resistance can be accomplished by modifying roughness. The surface roughness structure is one of the important parameters which greatly affects the flow of fluid through the cylinder surface. Fluid flow forms a vortex flow pattern with certain characteristics. Therefore, this study aims to analyze the characteristics and effects of fluid flow through the rough surface of the outer wall of the pipe with visualization using Particle Image Velocity (PIV). This research was conducted experimentally at the Faculty of Engineering, UHAMKA. The pipe surface roughness values varied were 0.648 µm and 1.699 µm. The length of the pipe used is 20 cm with a diameter of 2 inches. Measurements are made from the center of the pipe to a distance of 0.16 m. The results show that the surface roughness of the cylinder pipe affects the fluid flow characteristics where the formation of eddies is caused by the addition of the roughness value. The rougher the pipe surface is, the farther the vortex formation will be. The vortex formation closest to the pipe is a pipe with a roughness value of 0.648 µm at a distance of 0.04 m.